2009
DOI: 10.1097/anc.0b013e3181afab3c
|View full text |Cite
|
Sign up to set email alerts
|

Including Parents in the Evaluation of Clinical Microsystems in the Neonatal Intensive Care Unit

Abstract: Neonatal intensive care is an area of healthcare that has experienced significant growth in recent years. As a result, "megaunits" of more than 60 beds are not uncommon. Delivering care in units of this size that incorporates the principles of family-centered care and that is satisfying to both staff and parents is challenging. One proposed method to enhance delivery of care in the megaunit NICU has been to implement a clinical microsystem approach. Up to now, research to evaluate the efficacy of a clinical mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 24 publications
1
15
0
Order By: Relevance
“…Constraints on staff limit the time available for extensive parent counselling by physicians, leaving parents to depend on nurses to help explain their infant's status. [8] Reis et al [11] report that interaction with nurses and verbal and written information regarding the condition of infants were essential, and of course the method of communication was also of significance. It has also been observed that excessive information can lead to parental confusion, which therefore can decrease confidence in healthcare systems, increase anxiety and eventually decrease parental satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…Constraints on staff limit the time available for extensive parent counselling by physicians, leaving parents to depend on nurses to help explain their infant's status. [8] Reis et al [11] report that interaction with nurses and verbal and written information regarding the condition of infants were essential, and of course the method of communication was also of significance. It has also been observed that excessive information can lead to parental confusion, which therefore can decrease confidence in healthcare systems, increase anxiety and eventually decrease parental satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…This study is the first study of its kind, which prospectively planned the neonatal microsystem model of care in a large NICU to assess its potential risks and benefits in wide variety of aspects of health care. The prospective design of this trial helped us to address the identified characteristics of a high functioning microsystem through scheduled weekly meeting, inquiring feedback, providing information and continuing education so that essential elements of clinical microsystem could be maintained and positive culture could be fostered [4, 6]. …”
Section: Discussionmentioning
confidence: 99%
“…Advancement in neonatal care along with enhancement of life-saving technologies has resulted in the growth of neonatal intensive care units (NICU) in number and size [1, 2]. Development of large neonatal intensive units with over 40 beds, referred to as mega-units, has raised questions regarding their ability to maintain continuity and quality of care of these fragile patients [3, 4]. Increased rate of adverse events, provider burnout, strained infrastructure and impaired health system’s operation are among the potential risks associated with development of large NICUs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study by Reis et al, the parents stated that interaction with nurses and verbal and written information regarding the conditions of their infants were essential; of course, the method of communication was also of significance [17]. In some studies, it has been also revealed that information can lead to parental confusion; therefore, it can decrease confidence in health care systems, increase anxiety, and eventually decrease parental satisfaction [7,18]; these results are not consistent with the findings of the present study.…”
Section: Discussionmentioning
confidence: 99%